Incidence and risk factors of hepatocellular carcinoma after orthotopic liver transplantation - Colhoun, E. Dudley; Forsberg, C. Gunnar; Chavin, Kenneth D.; Baliga, Prabhakar K.; Taber, David J. (Surgery, 2017)
The incidence of hepatocellular carcinoma has doubled over the past 2 decades, becoming the fifth most common cancer worldwide. Orthotopic liver transplant is the gold standard treatment for those with hepatocellular carcinoma meeting eligibility criteria, although recurrence rates of hepatocellular carcinoma after orthotopic liver transplant still remain an understudied obstacle. We performed a single-center, retrospective, longitudinal study with the aim of determining the predominant baseline and follow-up variables associated with hepatocellular carcinoma recurrence. We gathered pre- and post-transplant data and conducted univariate and multivariate analysis to assess variables predicting hepatocellular carcinoma recurrence after orthotopic liver transplant. Between 2003 and 2015, 141 patients underwent orthotopic liver transplant for hepatocellular carcinoma. We identified 9 (6.4%) cases of documented hepatocellular carcinoma recurrence. Univariate analysis indicated that the difference in serum alpha-fetoprotein levels (most recent prior to transplant subtracted from maximum level) was lower in the hepatocellular carcinoma recurrence group (median 3 ng/mL vs 0 ng/mL, P = .052) as well as the pretransplant serum cholesterol level (median 158 mg/dL vs 113 mg/dL, P = .019) and days between hepatocellular carcinoma neoadjuvant treatment initiation and transplantation (median 122 vs 0, P = .045). Multivariate analysis revealed that a low pretransplant serum cholesterol level (<100 mg/dL) was independently associated with hepatocellular carcinoma recurrence (hazard ratio 11.0, P = .004). The risk of hepatocellular carcinoma recurrence after orthotopic liver transplant was low, at 6.4%, in this cohort. Low pretransplant serum cholesterol was the strongest predictor of recurrence and may help clinicians risk stratify patients for appropriate post-transplant monitoring and follow-up.